A Study on Extent of Utilization of Information and Communication Technology (Ict) among Farmers in Tirupathur District, India - E. Priyavadhana; T. Balakrishnan (Archives of Current Research International, 2025)
The growing complexity of agrarian challenges in India has exceeded the capacity of traditional public extension services, challenging the integration of Information and Communication Technology (ICT) to ground the knowledge gap. This study explores the extent of utilization of ICT tools among farmers in Tirupathur district of Tamil Nadu. A study was conducted across 10 villages using a proportionate random sampling method, with data collected from 120 respondents through a structured interview schedule. Findings indicates that major ICT tools included Television, Mobile phones, Agrisnet, TNAU AGRITECH portal, Paddy expert system, IFFCO Kisan, YouTube and WhatsApp which exhibited high engagement. Conversely, minor tools such as e-agricultural magazines, e-Krishi Kendra, AGMARKNET, Telegram and Twitter showed minimal usage highlighting the need for improved digital literacy and targeted awareness campaigns to enhance the adoption of underutilized ICT tools for effective knowledge dissemination in rural communities. Analyzing 13 personal, socio-economic, cognitive, behavioral, and skill-related factors that revealed farm size, information seeking behaviour, ownership of ICT gadgets, social participation and social media usage exhibit very strong positive correlations with ICT adoption, while occupational status shows a strong negative correlation underscoring the need for targeted interventions to improve digital engagement in agriculture and Education showed a very weak and non-significant relationship with ICT usage, indicating that formal education alone does not significantly influence the extent of ICT utilization among respondents. This study sheds light on the transformative eventuality of ICT in ultramodern extension services and its critical part in strengthening pastoral agrarian knowledge dispersion.